The influence of chronic diseases and poor working conditions in working life expectancy across educational levels among older employees in the Netherlands - Jolinda LD Schram; Merel Schuring; Karen M Oude Hengel; Alex Burdorf; Suzan JW Robroek (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: This study aims to estimate the influence of chronic diseases and poor working conditions - across educational levels - on working life expectancy (WLE) and working years lost (WYL) in the Dutch workforce after age 50. METHODS: Information on demographics, chronic diseases, and working conditions from 11 800 Dutch workers aged 50-66 years participating in the Study on Transitions in Employment, Ability and Motivation (STREAM) from 2010/2015 was enriched with monthly information on employment status from Statistics Netherlands up to 2018. In a multistate model, transitions were calculated between paid employment and involuntary exit (disability benefits, unemployment) and voluntary exit (economic inactivity, early retirement) to estimate the impact of education, chronic diseases, and working conditions on WLE and WYL between age 50 and 66. RESULTS: Workers with a chronic disease (up to 1.01 years) or unfavorable working conditions (up to 0.63 years) had more WYL due to involuntary pathways than workers with no chronic disease or favorable working conditions. The differences in WYL between workers with and without a chronic disease were slightly higher among workers with a lower education level (male: 0.85, female: 1.01 years) compared to workers with a high educational level (male: 0.72, female: 0.82 years). Given the higher prevalence of chronic diseases and unfavorable working conditions, WYL among lower educated workers were higher than among higher educated workers. CONCLUSIONS: The presence of a chronic disease or unfavorable working conditions, more prevalent among lower educated workers, contribute substantially to WYL among older workers. This will increase educational inequalities in working careers.eers.